2006
DOI: 10.1177/1362361306064403
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of social skills intervention based on interactive LEGO© play

Abstract: LEGO building materials have been adapted as a therapeutic modality for increasing motivation to participate in social skills intervention, and providing a medium through which children with social and communication handicaps can effectively interact. A 3 year retrospective study of long-term outcome for autistic spectrum children participating in LEGO therapy (N = 60) compared Vineland Adaptive Behavior Scale socialization domain (VABS-SD) and Gilliam Autism Rating Scale social interaction subscale (GARS-SI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 13 publications
6
84
0
8
Order By: Relevance
“…Social skills programs for higher-functioning children and adolescents Many controlled trials 21,23,24,29,[59][60][61][62][63][64][65] and observational studies 25,26,30,31,[66][67][68][69][70] of social skills programs have been conducted. We conducted several meta-analyses on social skills studies that used similar outcome measures.…”
Section: Lowmentioning
confidence: 99%
“…Social skills programs for higher-functioning children and adolescents Many controlled trials 21,23,24,29,[59][60][61][62][63][64][65] and observational studies 25,26,30,31,[66][67][68][69][70] of social skills programs have been conducted. We conducted several meta-analyses on social skills studies that used similar outcome measures.…”
Section: Lowmentioning
confidence: 99%
“…This is consistent with the theory that performance-training interventions provide somewhat more "enriched" social environments, facilitating greater in-session peer interaction (Lerner, Hileman, et al, in press;Lerner & Levine, 2007); this also suggests that it may be fruitful to consider that the process by which performance-training activities effect more enduring change in longer interventions (Legoff & Sherman, 2006;Lerner et al, 2011) may indeed accord with neuroplastic models of learning and intervention (Bryck & Fisher, 2012;Lillard & Erisir, 2011;Robertson & Murre, 1999;Rosenzweig, 2007). However, neither condition demonstrated generalization of effects to post-test unstructured social interaction or change in Theory of Mind or emotion recognition; this is somewhat unsurprising, as even four 90-minute sessions of these conditions failed to produce generalized results (Lerner & Mikami, in press).…”
Section: Clinical and Theoretical Implicationssupporting
confidence: 60%
“…Still others have demonstrated significant improvements in generalized (out-of-session) social skills among youth receiving creativity-focused social performance-training compared to matched controls engaging in social knowledge-training interventions after 3 years of continuous intervention in both groups (Legoff & Sherman, 2006). Likewise, creativity-focused social performance approaches have preliminarily demonstrated results in terms of improvements in social anxiety (Lerner, Calhoun, & Mikami, 2009;Lerner, Calhoun, Mikami, & De Los Reyes, in press) and autistic impairment in social settings (Lerner, Spies, Jordan, & Mikami, 2009).…”
Section: Social Skills Interventions For Hfasdsmentioning
confidence: 99%
“…Of these, 5 were conducted in the United States (62-66), one took place in the United Kingdom (67), and one occurred in Australia (68). Some of the studies included children (62,63,67,68), whereas others focused on adolescents (64)(65)(66).…”
Section: Social Skills Trainingmentioning
confidence: 99%
“…The only exception was the retrospective study of the Lego-based interactive playgroups (63), which included 60 participants in the intervention group. Although all 7 studies reported beneficial effects of the interventions, we assessed that the results should be interpreted with caution due to the small sample sizes and the non-randomized design.…”
Section: Social Skills Trainingmentioning
confidence: 99%